MAKNA KEMATIAN DALAM LIRIK LAGU ANAK “シャボン玉” (SHABON DAMA) KARYA NOGUCHI UJOU SEBUAH KAJIAN STRUKTURAL DAN SEMIOTIK - Agus Naryoso; Rukti Rumekar; Mj Rizqon Hasani (Vocational College of Diponegoro University, 2023)
This undergraudate thesis examines about the grief meaning of the lyric in Shabon Dama, so the data that used in this research is the lyric of the children song